2017
DOI: 10.1111/gcb.13715
|View full text |Cite
|
Sign up to set email alerts
|

Circumpolar dynamics of a marine top‐predator track ocean warming rates

Abstract: Global warming is a nonlinear process, and temperature may increase in a stepwise manner. Periods of abrupt warming can trigger persistent changes in the state of ecosystems, also called regime shifts. The responses of organisms to abrupt warming and associated regime shifts can be unlike responses to periods of slow or moderate change. Understanding of nonlinearity in the biological responses to climate warming is needed to assess the consequences of ongoing climate change. Here, we demonstrate that the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…The fact that the black-legged kittiwake was completely missing during the 2017 survey also coincides with a general decline among breeding populations in the North Atlantic (Descamps et al 2017). However, as with the alcids and the other gulls, only a small portion of the total winter range was covered during both surveys, so the difference may be due to geographical shifts within the overall wintering area.…”
Section: Apparent Changes In Distribution and Abundancementioning
confidence: 66%
See 1 more Smart Citation
“…The fact that the black-legged kittiwake was completely missing during the 2017 survey also coincides with a general decline among breeding populations in the North Atlantic (Descamps et al 2017). However, as with the alcids and the other gulls, only a small portion of the total winter range was covered during both surveys, so the difference may be due to geographical shifts within the overall wintering area.…”
Section: Apparent Changes In Distribution and Abundancementioning
confidence: 66%
“…piscivorous seabird species have declined in the eastern North Atlantic has accumulated (Frederiksen 2010;Ganter & Gaston 2013;Kuletz et al 2017). The declines appear to be linked to wide-ranging climate and ecosystem changes in the North Atlantic (Irons et al 2008;Descamps et al 2013;Frederiksen et al 2013;Descamps et al 2017). However, among planktonic and benthic feeders, some species are seemingly doing well and local changes are sometimes opposite to the general trend (Frederiksen 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To account for potential environmental effects on prey availability, we included sea surface temperature (SST) from island measurements recorded daily at noon in May, June, and July. Prey quality and availability in May will affect females forming eggs (Perrins 1970), and summer temperatures can affect breeding success, through prey availability for chicks (Carroll et al 2015, Descamps et al 2017).…”
Section: Environmental Variablesmentioning
confidence: 99%
“…One species in which spatial synchrony has been investigated is the black-legged kittiwake Rissa tridactyla (hereafter 'kittiwake'), a colonial, pelagic seabird species that has recently shown such steep declines that it was globally red listed (BirdLife International 2018). Over the scale of its full distribution across the Northern Hemisphere, synchrony in the fluctuations of colony sizes has generally been nonexistent or very low, apart from a synchronised decline during a period of rapid ocean warming (Descamps et al 2017). Similarly, a study looking at smaller scale synchrony, using colonies along the coast of Norway, found no evidence that colony sizes fluctuated in unison (Sandvik et al 2014).…”
Section: Introductionmentioning
confidence: 99%